INTENSITAS KOMUNIKASI ORANG TUA DAN PEER GROUP SUPPORT TERHADAP TINGKAT KETERBUKAAN MENCERITAKAN PENGALMAAN CYBERBULLYING - Tjen Maurilia Zerlina; Sunarto Sunarto; S. Rouli Manalu (Interaksi Online, 2022)
Internet technology become something that cannot be avoided in the current era. Unfortunately, the existence of the internet and technology also creates a new problem, namely cyberbullying. Cyberbullying is a problem that has not been completely resolved. UNICEF itself even states that the impact of cyberbullying greatly affects the mental, emotional, and physical aspects of individuals. This is something that cannot be eliminated directly. However, this can be minimized by raising awareness by various parties. This study used social penetration theory to explain each variable. On the other hand, this study also used a schema of relationships within the family to support the main theory. The sampling technique was purposive-sampling. The sample was 150 people with characteristics of people aged 16-25 years who had been victims of cyberbullying, lived in Semarang and actively used social media.. Tests in this study used multiple linear regression. The results showed that the influence of the intensity of parental communication on the level of openness in telling the cyberbullying experience was 26.6%. Meanwhile, the intensity of peer group support on the level of openness tells about the experience of cyberbullying by 5.7%. The intensity of parental communication and peer group support on the level of openness tells of the cyberbullying experience of 29.1%. with all the significance of the three variables below 0.01. This means, this study had an influence with different strengths on each variable.